Pengaruh Pelatihan Kader Kesehatan Jiwa Terhadap Pengetahuan dan Ketrampilan Kader di Wilayah Kerja Puskesmas Menteng - Missesa Missesa (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2022)
Nurses as health workers are responsible for overcoming mental health problems by working with mental health cadres. This study aims to determine the effect of mental health cadre training on the knowledge and skills of cadres in the working area of the Menteng Health Center. The research method used is quantitative research "Quasi-Experimental Pre-Post Test without Control Group. The sample in this study was 33 respondents using the purposive sampling technique. Univariate data analysis with frequency distribution and bivariate data analysis with dependent sample t-test. The results of the study showed that there was a significant increase in the knowledge and skills of cadres before and after the Mental Health Cadre Training with a value = 0.000. The suggestions from this study are that nurses holding mental health programs and mental health cadres can work together in creating a mentally healthy society.